(3OQGSI JMdjdjI ebGQfI dShb GdfbhO hSYQ GdUQas - (3fTCJ(B, (3Gdhcjds ((3GdbGgQI(B:s (3TQcI fGS ddWHGYI(B,s, 2006)
(3eOGNd JMOjO eYOd GdUQa,Shb GdfbhO heYOd GdUQa(B:(3OQGSI eSMjI,GdfeGPL GdfbOjI GdCSGSjI deYOd GdUQa,fehPLG JhGRf GdeMaXI hEMdGd GdYedI deYOd GdUQa,GdfehPL GdbjGSj hJMdjd GdfJGFLs
(3HHdjhZQGajG(B:(3U(B.443-452s
Keywords: (3GdfbhOs; (3SYQ GdUQas